Hyperthermal-driven anoxia and reduced productivity in the aftermath of the Permian-Triassic mass extinction: a case study from Western Canada - Woods, Adam D.; Zonneveld, John-Paul; Wakefield, Ryan (Frontiers in Earth Science, 2023)
The eruption of the Siberian Traps near the Permian-Triassic boundary (PTB) resulted in the rapid input of vast amounts of CO2 into the atmosphere and the subsequent development of a hothouse climate across much of the Early Triassic. The distribution of environmental stresses led to a complex recovery as survivors navigated high SSTs in shallow settings and an expanded OMZ that impinged upon the continental shelves. The Ursula Creek section of western British Columbia preserves a complete Lower-lowermost Middle Triassic sedimentary record of deepwater facies and provides a means to examine how offshore oceanic conditions varied along the western continental margin of Pangaea across the PTB and the entire Permian-Triassic recovery interval. A total of 204 samples were collected from the uppermost Permian Fantasque Formation, the Griesbachian -Dienerian Grayling Formation and the Smithian -Anisian Toad Formation and analyzed for major, minor, and trace elements in addition to %TOC contents. Anoxic to euxinic conditions were persistent during deposition of most of the study interval based on lithologic indicators (finely-laminated siltstone that lacks trace fossils and a benthic fauna) and elevated Mo, U, and V enrichment factors (EFs). Ba, Cu, Ni, P, and Zn EFs indicate dampened productivity (EFs < 1) across the much of the Early Triassic that was the result of weakened upwelling during a global hothouse interval. An increase in Cu, Ni, P, and Zn enrichment factors during the Anisian track a decline in global temperatures and the reestablishment of coastal upwelling as global thermal gradients and wind speeds increased. The results of this study point to the persistence of hyperthermal events and associated environmental stressors and underscores the urgency of curbing modern greenhouse gas emissions to prevent Earth from tipping into a hothouse state.